Desiring more: complicating understandings of sexuality in research processes. Issue 3 (19th June 2013) - Diprose, Gradon; Thomas, Amanda C; Rushton, Renee
<x xml:space="preserve">Abstract</x> Reflexively considering one's position when undertaking research has become commonplace in geographic research and writing. This phenomenon is linked to the increasingly prevalent view that research is a co‐constituted process that involves the participant and researcher both constructing meaning. Yet, curiously, there has been relatively limited discussion around the role that sexual experiences play in the research process. In this article we draw on three experiences to illustrate the complex ways in which unwanted sexual encounters with research participants can affect the research process. Through these stories we show how sexual encounters shaped the research process, unsettled the way we understood and performed our own gendered sexuality, and challenged our understandings of what it means to be 'good researchers'. We aim to initiate a wider discussion around how we can best prepare emerging researchers for, and support in the wake of, unexpected encounters of desire in the field.